Millennium manuscripts of hadith: Scholarship and methodology an analytical comparative study / Ibrahim Najm Abdulrahman - Ibrahim Najm , Abdulrahman (2021)
We have quite a number of millennium manuscripts of Hadith, some of which are considered original. However, a group of researchers questioned the authenticity of these manuscripts, while others claimed them unreliable since they were not based on a reliable methodology in dhabt (i.e., accuracy) and documentation. To answer these ambiguities, this study examined the methodology of Muhaditheen (Hadith narrators) in accuracy, verification and rectification in their early millennium manuscripts. The study followed inductive and analytical comparative method. It gathered opinions of Hadith narrators concerning the methodology of the manuscript accuracy and precision. Then, it searched for millennium manuscripts and managed to collect (149) manuscripts in Hadith. A number of (47) manuscripts were chosen to be analyzed, criticized and compared to set its methodology. Also, a group of principles and basics on which Hadith narrators of millennium manuscripts based their work were pointed out and compared with those stated in books of Hadith. This is to show the strong correlation between manuscript scholarship and Hadith terminology. This study concluded a number of significant additions in millennium manuscripts that were not mentioned by Hadith scholars in their books. Also, it stated the additions of Hadith scholars among themselves, their diversity and preferences in issues related to the accuracy and rectification of the manuscript by comparing between Hadith scholars in books of Hadith. It also showed that Hadith narrators used abbreviations and symbols in their manuscripts since early times of compilation; the oldest found in the 3rd Hijri century. As well as, the study gathered data of millennium manuscripts of Hadith found in public and private libraries for inspection and precise description. It was able to pin out some mistakes made by editors and indexers in describing these millennium manuscripts. The study described (149) millennium manuscript in Hadith.